The Therapeutic Potential of Neural Stem Cell in Ischemic Stroke: A Systematic Review - Periyanto, Toni; Putri, Evira Agustina; Romano, Sultan Adhitya; Riantiarno, Chairizia; Kamal, M. Aulady Rifki; Aulia, Indri Noer; Sugianto, Michael Aquilar (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Ischemic stroke remains a leading cause of disability and mortality worldwide, with over 12 million new cases annually and limited treatment options confined to narrow therapeutic windows. Neural stem cells (NSCs) have emerged as a promising therapeutic avenue due to their ability to self-renew, differentiate into all neural lineages, and exert paracrine effects that modulate inflammation and promote neurogenesis. Preclinical studies have demonstrated functional improvements of up to 60% in animal stroke models, but a systematic evaluation of these findings is needed to inform future clinical applications. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Databases searched included PubMed, EMBASE, and Scopus, covering literature up to May 8, 2025. Inclusion criteria comprised in vivo preclinical studies investigating NSC transplantation in animal models of ischemic stroke with at least one neurological, infarct, or histological outcome. Data extraction and risk of bias assessment (ROBINS-I) were independently performed by three reviewers. Due to study heterogeneity, a narrative synthesis was undertaken. Result: Eight studies met the inclusion criteria. NSC therapy improved neurological recovery in over 80% of cases, reduced infarct volume by up to 40%, and downregulated pro-inflammatory and apoptotic markers. Benefits were dose- and timing-dependent, with intracerebral and intravenous routes demonstrating variable efficacy. One study reported tumorigenicity, highlighting the need for safety profiling. Conclusions: Preclinical evidence supports the therapeutic potential of NSCs in ischemic stroke through neuroprotective and neurorestorative mechanisms. High-certainty findings justify continued investigation in clinical trials to refine dosing, delivery, and safety protocols.